(3CHYGO GdJcGed hGdJeGKd aj GdYdGbI Hjf GdTQY hGdhVYjI GdLfGFjI (B/s - (3BOe eMehO EHQGgje aJM GdHGHs; . (3YeQ eMeO SGdes; (3eMeO jhSa Mafjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2023)
(3JfJej gPg GdOQGSI Edi fhY ef GdOQGSGJ GdJj Jbhe Ydi GdebGQfI, hbO bUO GdHGMK Cf Jchf gPg GdebGQfI ef GdefXhQ GdadSaj aj GdfWGb GdLfGFj HMOhOg GdKdGKI, hgj GdeLQe hGdLQjeI hGdLRGA; agj HMlK dGSJXgGQ CHYGO GdhaGb hgj (B"(3CHYGO GdJcGed hGdJeGKd(B" (3hPdc (B"(3aj GdYdGbI Hjf GdTQY HGdhVYjI GdLfGFjI(B"(3, hYdGhkI Ydi chf GdHMK OQGSI adSajI; aEfg Ph WHjYI abgjI hdjSJ bGfhfjI, Cj dG fHMK hLgJj fXQ bGfhfjI, hdG fbGQf Hjf GdbhGfjf aj UhQgG GdJTQjYjI GdJj GfHKbJ Yf GdTQjYI GdESdGejI ef fGMjI, Ch fXjQJgG GdeYGUQI ef fGMjI CNQi, Hd fMGhd Cf fHMK GdCHYGO GdadSajI Hjf GdTQY GdLfGFj hGdhVYjI GdLfGFjI ef NdGd GdMOhO KdGKI, gj GdeLQe, hGdLQjeI, hGdLRGA, hHYO Cf fJHjfgG ef efXhQ cd abmg Ydi MOI fMGhd Cf fJHjf hLg GdYdGbI HjfgeG, gd jYhPgG GdJcGed h GdJeGKd, Ce Cnqf gPjf GdCNjQjf jTcdGf CHYGO GdYdGbI HjfgeG(B. (3Enqfg djS gfGc eG jefY ef LgI GdYbd Ch ef LgI GdTQY Cf jfgd Gdabg GdLfGFj GdTQYj ef GdfHY GdhVYj GdLfGFj GdeJMVQ, hPdc dHdhZ GdMGdI GdYUQjI ef GdJWhQ HGdGLJgGO, hPdc gh eG fbUOg ef HYO GdJcGed aj GdYdGbI Hjf GdTQY hGdhVYjI GdLfGFjI; ceG Cf GdWGHY GdQhMj Ch GdEjeGfqj ddTQY GdLfGFj gh GdWQjb GdPj faP Hg Edi eG hQGA GdWHjYI MjK Gdchf hCSQGQg, hdeG dG hgj JfRjd GdYRjR GdMcje GdPj Ndb Gdchf hGdWHjYI heG ajgeG, heeGKdI GdhVYjI GdLfGFjI dPdc GdTQY aj eYGdLGJgG EfeG jYfj Cf GdTQY CJe YdjgG eHJZGgG bOjeG, EP bGeJ GdhVYjI HMkKG Yf eKGd WHjYj JSeh Edjg, hgh GdPj OaYfG Edi Gdbhd Cf GdQcf GdQhMj hLGfHg gh GdPj cnqed Hg GdTQY fXjQg GdhVYj, djSeh Hg MjK cGf jJWdY GdadGSaI GdoCnhd(B. s
This study belongs to a kind of studies that are based on comparison. The researcher intended that this comparison be from a philosophical perspective in the criminal domain with its three limits, which are the criminal, the crime, and the penalty. It is a research to memorize the dimensions of concord, which are the "dimensions of integration and symmetry" and that "in the relationship between Sharia and the criminal situation", and in addition to the fact that the research is a philosophical study; It is of a jurisprudential nature and not a legal one, that is, we do not discuss two legal points of view, and we do not compare laws in their legislative forms that emerged from Islamic Sharia on the one hand, or their contemporary counterparts on the other hand. Rather, we try to examine the philosophical dimensions between the criminal law and the criminal situation through the three limits, which are the criminal, the crime, and the penalty. dimensions of their relationship. There is nothing that prevents, on the one hand, on the one hand, or on the one hand, from the Shari'a, that legal criminal jurisprudence draws from the positivist, criminal, civilized source, in order to reach the modern state of development through jihad, and that is what we mean after integration in the relationship between Sharia and the criminal situation; Likewise, the spiritual or faith-based nature of the criminal law is the path by which it penetrates beyond nature, where the universe and its secrets are, and why not, which is the revelation of the Almighty, the Wise, who created the universe and nature and what is in them, and the similarity of the criminal situation to that law in its treatment means that the law fulfilled its desire in the past. As positivism arose in search of a natural ideal to rise to, and this is what prompted us to say that the spiritual pillar and its aspect is the one with which the Sharia complemented its positivist counterpart, to elevate it as the first philosophers aspired.
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2023. s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ (B327-349.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdTQY hGdhVYjI GdLfGFjIs; (3GdhVY GdLfGFi GdeJMVQs; (3GdJcGed hGdJeGKds; (3GdCHYGO GdadSajI s; (3eUGOQ GdTQY GdLfGFjs; (3Gdeaghe GdSaSWGFj ddYOds; (3OhQ GdYbd GdSbQGWjs; (3GdTQjYI GdjghOjI GdLfGFjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs